RETRACTED: State and debris of trees of afforestation belts in arid conditions of the Southern part of Central Siberia - Vais A.A.; Batvenkina T.V.; Shevelev S.L.; Artemyev O.S.; Vorobeva I.A.; Romanova L.I.; Motyrev N. O. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001